Hemodynamics through the congenitally bicuspid aortic valve: a computational fluid dynamics comparison of opening orifice area and leaflet orientation. (November 2016) - Mei, Sen; de Souza Júnior, Francisco S.N.; Kuan, May Y.S.; Green, Naomi C.; Espino, Daniel M.
A computational fluid dynamics model of a bicuspid aortic valve has been developed using idealised three-dimensional geometry. The aim was to compare how the orifice area and leaflet orientation affect the hemodynamics of a pure bicuspid valve. By applying physiologic material properties and boundary conditions, blood flow shear stresses were predicted during peak systole. A reduced orifice area altered blood velocity, the pressure drop across the valve and the wall shear stress through the valve. Bicuspid models predicted impaired blood flow similar to a stenotic valve, but the flow patterns were specific to leaflet orientation. Flow patterns developed in bicuspid aortic valves, such as helical flow, were sensitive to cusp orientation. In conclusion, the reduced opening area of a bicuspid aortic valve amplifies any impaired hemodynamics, but cusp orientation determines subsequent flow patterns which may determine the specific regions downstream from the valve most at risk of clinical complications.